Occurrence and Distribution of a Diatom-Diazotrophic Cyanobacteria Association during a Trichodesmium Bloom in the Southeastern Arabian Sea. (6th August 2013) - Jabir, T.; Dhanya, V.; Jesmi, Y.; Prabhakaran, M. P.; Saravanane, N.; Gupta, G. V. M.; Hatha, A. A. M.
Abstract : Symbiotic diatom-diazotrophic cyanobacteria association (DDA) of Rhizosolenia hebetata and Rhizosolenia formosa with endosymbiotic cyanobacteria Richelia intracellularis was noticed and documented for the first time during a bloom of the cyanobacterium Trichodesmium erythraeum in the oligotrophic shelf waters along Kochi and Mangalore transects, southeastern Arabian Sea (SEAS), during spring intermonsoon (April 2012). Although the host is frequently seen, the symbiont is rarely reported in the Indian EEZ. The presence of nitrogen-fixing symbiotic association of Rhizosolenia-Richelia along with Trichodesmium erythraeum highlights the significance of DDAs on the nutrient and energy budgets of phytoplankton in the oligotrophic environments of the Arabian Sea during spring intermonsoon.